High-Performance Flexible Bottom-Gate Organic Field-Effect Transistors with Gravure Printed Thin Organic Dielectric - Vaklev,NL; Müller,R; Muir,BVO; James,DT; Pretot,R; van,der Schaaf P; Genoe,J; Kim,J-S; Steinke,JHG; Campbell,AJ (Advanced Materials Interfaces, 2014)
Gravure-printed dielectric films are presented, which are 100-nm thick, have about 1-nm root mean-square surface roughness and show high electric field strength (>300 MV/m). This dielectric is combined with an ultra-thin—less than 10 nm—layer of poly(α-methylstyrene) on top which gives state-of-the-art field-effect mobility in transistors with thermally-evaporated pentacene (0.6 cm2/Vs) and zone-cast TIPS-pentacene (0.3 cm2/Vs).